Effects of printing in the reconquest of new granada: The republicanization of public opinion and the rationalization of the monarchy (2017)
In the middle of the eighteenth century, the first printing press arrived at New Granada, due to the Jesuit congregation. But it was at the end of that century when, on the occasion of the earthquake that struck the capital, the Earthquake Warning appeared, the country's first newspaper which reached a great popularity. In this sense, in the following article of reflection, we analyze the effects of printing in the public opinion of New Granada in the period of The Spanish Reconquest. Through the study of primary and secondary sources, we conclude that the work of printing was fundamental to blur the symbolic dominance of the monarchy by partially integrating the popular classes into general deliberation, participation and relative transparency over tasks of government.